Pola Tidur yang Buruk Meningkatkan Risiko Hipertensi - Martini, Santi; Roshifanni, Shofa; Marzela, Fanni (Media Kesehatan Masyarakat Indonesia, 2018)
Poor sleep patterns of sleep disturbances, poor sleep quality, and short sleep duration may increase the risk of hypertension. Hypertension itself is now a disease that occupies a high position that is often experienced by the community. The purpose of this study was to determine the relationship of poor sleep patterns behavior increases the risk of hypertension. This research was an observational research that is analytic with case control design. The sample in this study amounted to 76 people consisting of patients with hypertension and non hypertension patients in Public Poly, Primary Haelth Care Tanah Kalikedinding Surabaya. The sampling technique was done using simple random sampling. The result of the research using logistic regression test showed (p 0,000; OR 9,022) that sleeping pattern has the greatest influence to the happening of hypertension compared to age and gender. The strength of the influence of sleep patterns of respondents showed that respondents who had a good pattern had a 9.022 times greater risk of not having hypertension than those who had poor sleep patterns. Poor sleep patterns include sleep disturbances, poor sleep quality, and short sleep duration. Recommendations given to respondents who have bad sleep patterns should improve sleep patterns with a healthy lifestyle that is sleeping as needed and keep the mind so as not to experience pressure because of excessive stress.